Challenges facing the human rights treaty body system - A E Koneva (RUDN Journal of Law, 2014)
The human rights treaty bodies - international organs controlling the implementation of core international human rights treaties by States and forming an interlinked system today - are being confronted by a number of compelling challenges that seriously undermine their effective functioning. The current treaty body strengthening process aims to enhance the work of the treaty body system in a way that these challenges are addressed in most efficiently. In these terms the legal assessment of the system’s problems is essential for finding mechanisms of their solution that would ultimately improve human rights protection at the national level.